Penerapan Metode Blanded Learning Ditinjau dari Teori Konektivisme - Cahyono, Dedi Dwi; Mustofa, Nurul Hadi; Fauziati, Endang (YASIN, 2022)
Education is the main key for a country to excel in global competition. Education is considered as the most strategic field to realize national welfare. In the world of education, there are various learning methods, including according to the thoughts of international education figures. To respond to situations like this, teachers use one of the appropriate learning models during the pandemic by using blended learning. Connectivism's view has implications in all aspects of life. Connectivism is driven by the understanding that decisions are based on rapid change. New information is obtained continuously, as well as the ability to determine between important and unimportant information.